Integral Sliding Mode Controller for PMSM Single Current Flux-Weakening Control - Cao Yu; Chi Song (机车电传动)
An improved sliding mode speed controller was presented for flux-weakening control of permanent magnet synchronous machine (PMSM) based on single current regulation algorithm, to improve the controllability of the speed of the single current regulator. The integral sliding surface was designed, which results in the elimination of chattering and the declination of the speed error and the robustness to parameter disturbance and load variation in the flux-weakening area. Based on the d-q current cross-decoupling effect, the proposed control combined single-current regulator algorithm and sliding mode control. The scheme was verified by computer simulation using PLECS software analysis.